Performance of a tool to identify different types of self-reported sexual risk among women attending a contraception and sexual health clinic: results of a cross-sectional survey. Issue 2 (4th June 2020) - Edelman, Natalie; Whetham, Jennifer; Cassell, Jackie; de Visser, Richard; Mercer, Catherine; Jones, Christopher; Gersten, Abbey; Bremner, Stephen
Abstract : Introduction: A clinical prediction rule (CPR) using psychosocial questions was previously derived to target sexual healthcare in general practice by identifying women at risk of unintended pregnancy (UIP) and sexually transmitted infections (STIs). This psychosocial CPR may help target resources within contraception and sexual health (CASH) services. This study investigated how well it predicted recent self-reported risk of UIP and STI acquisition among women attending a CASH clinic. Methods: Female patients aged 16–44 years attending a CASH clinic in South-East England were offered a questionnaire on arrival. This comprised psychosocial questions, and others addressing three sexual risks: (1) two or more male sexual partners in the last year (2+P), (2) risk of STI acquisition through most recent partner and (3) risk of UIP in the last 6 months. A CPR score was calculated for each participant and cross-tabulated against self-report of each sexual risk to estimate CPR sensitivity and specificity. Results: The psychosocial questions predicting 2+P had sensitivity 83.2% (95% CI 79.3% to 86.5%) and specificity 56.1% (95% CI 51.3%−60.6%). Those predicting combined 2+P and/or risk of STI acquisition through most recent partner had a sensitivity of 89.1% (95% CI 85.7%−91.8%) and specificity of 43.7% (95% CI 39.0%−48.5%). Questions predicting risk of UIP in the last 6 months had a sensitivity of 82.5% (95% CI 78.6%−86.0%) and specificity of 48.3% (95% CI 43.4%−53.1%). Conclusions: The CPR demonstrated good sensitivity but low specificity, so may be suited to triaging or stratifying which interventions to offer CASH patients and by which mode (eg, online vs face-to-face). Further investigation of causal links between psychosocial factors and sexual risk is warranted to support development of psychosocial interventions for this patient group.